Dok-7/MuSK signaling and a congenital myasthenic syndrome. - Yamanashi, Y; Higuch, O; Beeson, D (2008)
Skeletal muscle contraction is controlled by motor neurons, which contact the muscle at the neuromuscular junction (NMJ). The formation and maintenance of the NMJ, which includes the aggregation of densely packed clusters of acetylcholine receptor (AChR) opposite the motor nerve terminal, is orchestrated by muscle-specific receptor tyrosine kinase, MuSK. Recently, a MuSK-interacting cytoplasmic adaptor-like protein Dok-7 was identified and its localization at the postsynaptic region of the NMJ was revealed. Mice lacking Dok-7 have a phenotype indistinguishable from MuSK-deficient mice, and fail to form both AChR clusters and NMJs. In cultured myotubes, Dok-7 is required for MuSK activation and AChR clustering. Thus, Dok-7 is essential for neuromuscular synaptogenesis and it appears that the regulatory interaction of Dok-7 with MuSK is integrally involved in this process. In humans there are both autoimmune and genetic causes of defective neuromuscular transmission that gives rise to the fatigable muscle weakness known as myasthenia. DOK7 has been found to be a major locus for mutations that underlie a genetic form of myasthenia with a characteristic 'limb girdle' pattern of muscle weakness (DOK7 CMS). Patients with DOK7 CMS have small, simplified NMJs but normal AChR function. The most common mutation causes a COOH-terminal truncation, which greatly impairs Dok-7's ability to activate MuSK. Recently, a series of differing DOK7 mutations have been identified, which affect not only the COOH-terminal region but also the NH2-terminal moiety. The study of these mutations may help understand the underlying pathogenic mechanism of DOK7 CMS.